Reading Psalm 100 from an African (Yoruba) perspective - Adamo, David Tuesday (Journal for semitics, 2018)
Psalm 100 is one of the most popular psalms of praise and thanksgiving. Almost every scholar accepts this psalm as a hymn commanding the congregation to praise Yahweh in thanksgiving. This song is so vital because to praise and worship Yahweh is to live and to live is to praise and worship him for his majesty and all the things he has done for ancient Israel. Psalm 100 is also called the imperative psalm because of the seven imperative verbs that seem to dictate its structure. The content of this psalm not only resembles ancient Israelite worship but also typical African worship. This article aims to apply an Africentric interpretation to Psalm 100 in order to demonstrate how the praise and worship in African churches reflect the description of Psalm 100 (without saying that they are the same). This article aims to demonstrate how African religion and culture can be used to understand Psalm 100 without condemning Eurocentric approaches.